(untitled) (Revista Española de Fisiología, 1994)
This study employs the isolated perfused rat pancreas to investigate the actions of the two gut hormones, cholecystokinin-octapeptide (CCK-8) and secretin on pancreatic juice flow and total protein output. Perfusion of the pancreas with either CCK-8 (100 pM) or secretin (100 pM) resulted in marked both pancreatic juice flow and total protein output. The effect of CCK-8 was three-fold larger compared to the responses obtained with secretin alone. Simultaneous application of CCK-8 and secretin (all 100 pM) failed to elicit either a potentiation or an additive effect in both pancreatic juice flow and total protein output. The net increases in both secretory parameters were reduced during combined application of CCK-8 and secretin compared to the responses obtained with CCK-8 alone. The results indicate that optimal concentrations of either CCK-8 or secretin can display marked secretagogue effects on the exocrine pancreas but when administered simultaneously they failed to elicit either an additive response or a potentiation in pancreatic juice secretion.